Some Properties of TiO2/Au Nanocomposite Thin Films Produced by Spincoating Method for Application in Plasmonic Solar Cells - Thien, Nguyen Duy; Thanh, Nguyen Tien; Thuy, Nguyen Tien; Vu, Le Van; An, Dao Khac (VNU Journal of Science: Mathematics - Physics, 2015)
The TiO 2 /Au nanocomposite thin films play a very important role in the plasmonic solar cell. In such as composite systems, the localized surface plasmon resonance (LSPR) of embedded metal nanoparticles determines the light absorption enhancement of the semiconductive part (TiO 2 ); hence, enhances the efficiency of the plasmatic solar cell. The characterizations of the TiO 2 /Au nanocomposite thin films – such as light absorption, scattering and LSPR capacities - depend on many parameters: sizes, weight ratio of metal nanoparticles, thickness of the thin film layers and the arrangements of TiO 2 /Au composite in integrated-matrix system. In this work, we outline the preparation method of the TiO 2 /Au nanocomposite thin films, then we investigate the effect of technological conditions – such as TiO 2 /Au mixture solution concentration, TiO 2 /Au weight ratio and number of spin-coating layers – to the surface morphology of the nanocomposite to find out the optimum fabrication conditions. Some experimental results of thin film such as structural property (X ray diffraction, thin film morforlogy…) and optical property (absorption coefficience concerning LSPR…) will also be shown and discussed. Keywords: TiO 2 /Au thin film, LSPR, plasmonic solar cell.